2005
DOI: 10.1080/00103620500303616
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Turbidimetric Potassium Test Modified for Use with the Pressurized Hot‐Water Extraction

Abstract: Colorimetric or turbidimetric quantification of soil potassium (K) coupled with pressurized hot-water (PHW) extraction could provide an inexpensive alternative to standard methods for small-scale farmers in developing countries. Two of many methods for K analysis, one using sodium tetraphenylborate and the other using sodium cobaltinitrite, were modified for use with PHW extraction and evaluated for the following requirements: readable on the spectrophotometer, minimal equipment requirement, rapid, simple, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
2
10
2
Order By: Relevance
“…This is expected, because mass action extraction can readily occur with ammonium acetate but not with PHW. The high correlation between AA and cobaltinitrite observed in this study was confirmed by Crane et al (2005) on 38 arid-zone soils.…”
Section: Comparison Of Methodssupporting
confidence: 89%
See 4 more Smart Citations
“…This is expected, because mass action extraction can readily occur with ammonium acetate but not with PHW. The high correlation between AA and cobaltinitrite observed in this study was confirmed by Crane et al (2005) on 38 arid-zone soils.…”
Section: Comparison Of Methodssupporting
confidence: 89%
“…This correlation is poorer than that reported by Crane et al (2005) (r 2 of 0.67; p , 0.0001) using the same procedures for 38 arid-zone soils from the western United States. Hanks, Webb, and Jolley (1997), who used sodium bicarbonate as the standard extractant, also observed better correlations (r 2 of 0.72), but their soils had naturally high K concentrations, whereas the Moroccan and Guatemalan samples included soils with low K levels.…”
Section: Comparison Of Methodscontrasting
confidence: 81%
See 3 more Smart Citations